Pengembangan Sistem Informasi Geografis Berbasis Web untuk Pendataan Kelompok Rentan dan Koordinasi Relawan - Pakaya, Nikmasari; Syafiullah, Zaiem Athif; Tuloli, Mohamad Syafri; Takdir, Rahman; Ahaliki, Budiyanto; Dwinanto, Arif (Universitas Negeri Gorontalo, 2025)
The manual process of collecting and distributing aid for persons with disabilities at Yayasan Putra Mandiri Gorontalo had faced challenges, including inefficiency, data inaccuracy, and weak coordination. These problems had impacted the accuracy and effectiveness of aid distribution. This study had offered a solution through a centralized web-based Geographic Information System (GIS) that integrated data, volunteer management, and location mapping. The contribution of this study was a system design that improved data accuracy and aid distribution effectiveness. The research used the Waterfall model, consisting of requirement analysis, system design with UML, implementation using PHP and MySQL, and black-box and white-box testing. The results showed that the system successfully performed CRUD operations, displayed interactive maps, and facilitated structured coordination. White-box testing indicated that the program logic complied with cyclomatic complexity. This system had supported better data quality and operational efficiency. The study concluded that the developed system was effective for managing aid distribution and could be further enhanced with automatic notification features